SEED BANKS IN A SUBTROPICAL RAIN FOREST - Abdulhadi, Rochadi (Research Center for Biology, 1992)
The seasonal populations and vertical distribution of seed banks in a subtropical rain foirest were assesed. No seasonal variations were indicated in either the species composition or the size of seed bank over a year period. The number of seeds were 550 - 603 m square, and mostly composed of secondari species. This population decreased with increasing soil depths.